2019
DOI: 10.1080/08998280.2019.1686912
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy and acute manic attack

Abstract: Takotsubo cardiomyopathy predominantly occurs in women, with a high incidence in patients with psychiatric diseases. We present a 64-year-old white woman with an acute manic episode complicated by rhabdomyolysis and takotsubo cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…3 For example, an investigation by The International Takotsubo Registry showed that patients with TTS had significantly higher rates of depression and anxiety compared with controls, 1 while another study reported higher rates of major depressive disorders in TTS patients compared with controls but not anxiety disorders 4 and another study showed higher rates of anxiety but not depression compared with controls. 5 Previous studies have reported cases of TTS related to acute manic attacks [6][7][8] or to an underlying bipolar disorder. 9,10 The exact aetiology of TTS is still unknown, but one hypothesis is that psychiatric illness and chronic stress could activate the hypothalamic-pituitary-adrenal (HPA) axis, increasing release of catecholamines, 11 and subsequently causing TTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 For example, an investigation by The International Takotsubo Registry showed that patients with TTS had significantly higher rates of depression and anxiety compared with controls, 1 while another study reported higher rates of major depressive disorders in TTS patients compared with controls but not anxiety disorders 4 and another study showed higher rates of anxiety but not depression compared with controls. 5 Previous studies have reported cases of TTS related to acute manic attacks [6][7][8] or to an underlying bipolar disorder. 9,10 The exact aetiology of TTS is still unknown, but one hypothesis is that psychiatric illness and chronic stress could activate the hypothalamic-pituitary-adrenal (HPA) axis, increasing release of catecholamines, 11 and subsequently causing TTS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported cases of TTS related to acute manic attacks 68 or to an underlying bipolar disorder. 9,10 The exact aetiology of TTS is still unknown, but one hypothesis is that psychiatric illness and chronic stress could activate the hypothalamic-pituitary-adrenal (HPA) axis, increasing release of catecholamines, 11 and subsequently causing TTS.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank the authors of the letter for their interest in our paper. 1 Mental disorders are a major cause of morbidity, and patients with mental health disorders have a higher incidence of takotsubo cardiomyopathy (TC). We agree with the authors that our patient had a combination of both emotional and physical stressors.…”
Section: The Authors Respondmentioning
confidence: 99%
“…However, nephrogenic systemic fibrosis and acute kidney injury due to primary excretion of gadolinium from the kidneys and various cardiac arrhythmias including QTc electrocardiographic prolongation and hypersensitivity reactions are occasionally encountered with use of such contrast mediums. 1…”
Section: Reader Commentsmentioning
confidence: 99%
“…Over the past several years, takotsubo cardiomyopathy (TC) has been the focus of interest as a transient form of cardiomyopathy generally emerging in response to a variety of emotional and physical stressors associated with adrenergic discharge. 1,2 In their recently published elegant article, 1 Idris et al reported a unique case of TC due to an acute manic attack. However, we would like to make a few comments on potential implications of TC in this specific setting.…”
mentioning
confidence: 99%